HUBUNGAN WHOLE BODY VIBRATION DENGAN DISABILITAS LOW BACK PAIN PADA PENGEMUDI OJEK - Kusuma Hadi; Purnamawati Tjhin (Jurnal Akta Trimedika, 2024)
Background. Low Back Pain (LBP) is a syndrome that occurs in the waist precisely in the lumbosacral region of the spine and belongs to the group of work-related musculoskeletal disorders. It is estimated that around 43% of the entire Indonesian population experiences LBP. Whole Body Vibration (WBV) is a mechanical vibration produced by a vibrating field such as when a person drives. These vibrations can be transmitted throughout the body and become one of the risk factors for LBP disability, in addition to length of driving, age and Body Mass Index. The purpose of this study was to assess the relationship between WBV and NBP in online motorcycle taxi drivers. Method. This study used a cross-sectional design on 101 online motorcycle taxi drivers in the West Jakarta area. LBP disability data was obtained through filling out the Oswestry Dissability Index (ODI) questionnaire and measuring WBV was carried out with a vibration meter. The analysis was performed with a Chi-square test using SPSS version 27. Result. The age range of respondents is between 20-60 years with the largest population in the age range of 31-40 years (38.6%). Most respondents felt WBV in the extreme uncomfortable category (56.4%) and 72.28% of respondents experienced back pain disability in the severe to very severe category. Analysis of the relationship between WBV and LBP disability was obtained p = 0.001. Conclusion. There is a significant relationship between WBV and LBP disability. The greater exposed to WBV, people have the higher risk of developing LBP disability.